Pengaruh Pembelajaran Berbasis Multiliterasi Terhadap Kemampuan Berpikir Kritis - Rosidah, Cholifah Tur (Universitas Nusantara PGRI Kediri, 2018)
This research is study to know is there any influence learning multiliteracy based on ability to think critically students. This study is backed by the lack of competence of ability to think critically students. In writing this article used quantitative research design with the form of the Quasi Eksperimental Design tipe of Non-Equivalent Control Group Design. Population in this research is all the students who study Learning Indonesian Language which devided in A, B, C, D, and E class. But, chosen sample appropriate to a purpose is class B as a experiment class and class C as a control class. Technique to collect data was throught pretest and posttest that contains about matter learning Indonesian Language in elementary school. The test had previously been through with a score 1of the practical and realiabilitas test with a score 0,685. The score is indicated that instrument test has been valid and it is reliable. Furthermore, the data which has been obtained analiyzed by using a technique test-t with the score 0,036 which had previously been preceded by do the normality test. The score is indicated that data is normal. The result of next a hypothesis that get the result H0rejected,that means that learning multiliteracy up a critical thinking tool in the ability of the students